Building knowledge with theory: Unpacking complexity in doctoral writing - Wilmot, Kirstin (Critical Studies in Teaching and Learning, 2023)
The use of theory to analyse and interpret empirical data is a valued practice in much social science doctoral research. A crucial aspect of this practice involves generating sophisticated theoretical understandings and critiques of phenomena in our social world. Despite the importance of theory, however, few concrete explanations of how to ‘theorise’ exist in literature. This paper addresses this gap by demonstrating how a set of conceptual tools can be used to unpack what the craft of theorising looks like in explicit terms, and to reveal how this ability develops over time during the drafting process of dissertation writing. It does this by drawing on select texts from a successful doctoral dissertation, as well as an earlier draft version. In doing so, the paper provides an in-depth explanation of an essential process of doctoral research that is inherently known by many supervisors, yet seldom unpacked in explicit terms.